One Year Incidence of Iatrogenic Atrial Septal Defect After Cryoballoon Ablation for Atrial Fibrillation. (3rd October 2013) - SIEIRA, JUAN; CHIERCHIA, GIAN‐BATTISTA; DI, GIACOMO; CONTE, GIULIO; DE, CARLO; SARKOZY, ANDREA; DROOGMANS, STEVEN; BALTOGIANNIS, GIANNIS; SAITOH, YUKIO; CICONTE, GIUSEPE; LEVINSTEIN, MOISES; BRUGADA, PEDRO
Atrial Septal Defect After AF Cryoballoon Ablation Introduction Pulmonary vein (PV) isolation by means of cryoballoon (CB) technology is an effective treatment for symptomatic paroxysmal atrial fibrillation (AF) refractory to antiarrhythmic drug therapy. The CB requires a 15F transseptal sheath that may lead to the creation of a iatrogenic atrial septal defect (IASD). Methods and Results Individuals having undergone PV isolation by the means of CB ablation and a subsequent transesophageal echocardiography (TEE) examination during postablation follow‐up were consecutively included. Thirty‐nine patients formed the study group (31 male, 76.9%; mean age 57.4 ± 13.7 years). IASD was present in 8 (20%) of them after a mean follow‐up time of 11.7 months. Mean diameter of the defect was 0.57 cm × 0.48 cm; only left to right shunt was observed. No adverse events were recorded in these patients during the follow‐up. Conclusion IASD after CB ablation of AF is present in up to 20% of patients after 1 year. Although no adverse clinical events were recorded in patients with persistence of IASD, this complication should not be underestimated and systematic echocardiographic examinations might be advised at regular intervals in the follow‐up period after CB. Further studies with larger population and follow‐up might be required to confirm our findings.